Professores pesquisadores na Comunidade de Prática em rede: espaço de colaboração - Muñoz, Cleide Maria dos Santos (2019)
This research aims to analyze how the Community of Practice (CoP) network in the Rede de Pesquisa Colaborativa Universidade Escola (University-School Collaborative Research Network) is organized. It is a project promoted by the Post- Graduate Program in Education: Curriculum from the Pontifical Catholic University of São Paulo (PUC-SP), which proposed a collaborative work between partner universities and public schools from different regions in Brazil by establishing a research network that linked students’ knowledge building to research practice. The theoretical framework of this thesis focuses on the concepts of community (WEBER, 1987; TÖNNIES, 1995; BAUMAN, 2003; PINTO, 2009; MOCELLIM, 2011) and community of practice (WENGER, 2001; PINTO, 2009); network (LÉVY, 1997, 1999, 2000; CASTELLS, 1999, 2003, 2010; SIMÕES, 2009) and social networks (PARENTE, 2000; MARTELETO, 2001; COSTA, 2003; HARDAGH, 2009; CORRÊA, 2011); collaboration (KENSKI, 2003; COMASSETTO, 2006; MANDAJI, 2011) and co-learning (RABELLO; OKADA, 2014; OKADA et al., 2012). This study was developed based on the qualitative approach (CHIZZOTTI, 2008; LÜDKE; ANDRÉ, 2018) consisting of a case study (CHIZZOTTI, 2008; LÜDKE; ANDRÉ, 2018; GIL, 2008). The guiding methodological procedure was the documental research through content analysis (CHIZZOTTI, 2008; GIL, 2008) of digitally collected data. Data analysis and interpretation were conducted based on maps and word trees generated by NVivo 12 software, which highlighted the most frequent terms and their contexts at the Edmodo platform forum, which is an interaction space between teachers and researchers. The interactions that occurred via WhatsApp also complement this analysis. The results show the presence of the three characteristics of a CoP (engaging, joint enterprise and shared repertoire), and that the teachers worked collaboratively while co-learned. They reinvented themselves and transformed their practice, thus becoming autonomous and not requiring coordination to mediate urgent situations